2019
DOI: 10.1039/c9ta04592a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical impedance spectroscopy as a performance indicator of water dissociation in bipolar membranes

Abstract: Using electrochemical impedance spectroscopy, we observed the rate of water dissociation decrease in the presence of salt ions while observing the transport of these salt ions, showing a clear link between the peaks observed in EIS and ion crossover.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…The degradation in BPM−electrode assembly systems can be associated with the stability of the water dissociation catalysts at the interface. Blommaert et al 39 used electrochemical impedance spectroscopy to investigate the degradation of BPM. Their results during the 5 days of measurement indicated that the ohmic resistance increased by up to 10% at OCV and 32% when applying current.…”
Section: Bpm Properties As Design Criteriamentioning
confidence: 99%
“…The degradation in BPM−electrode assembly systems can be associated with the stability of the water dissociation catalysts at the interface. Blommaert et al 39 used electrochemical impedance spectroscopy to investigate the degradation of BPM. Their results during the 5 days of measurement indicated that the ohmic resistance increased by up to 10% at OCV and 32% when applying current.…”
Section: Bpm Properties As Design Criteriamentioning
confidence: 99%
“…When a reverse bias is applied ( i.e. , when the CEL faces the cathode), the protons and hydroxide ions are removed from the IL through the CEL and AEL, respectively, which keeps the WDR to proceed. …”
Section: Introductionmentioning
confidence: 99%
“…Each point on the Nyquist plot represents a distinct frequency that decreases from left to right [41,47]. Explicitly, the Nyquist plot does not tell us about the frequency corresponding to an impedance.…”
Section: Electrochemical Impedance Spectroscopy Of Pdnps-azomentioning
confidence: 99%